2013
DOI: 10.1021/ol3034065
|View full text |Cite
|
Sign up to set email alerts
|

Myriberine A, a New Alkaloid with an Unprecedented Heteropentacyclic Skeleton from Myrioneuron faberi

Abstract: Myriberine A (1) possessing an unprecedented carbon skeleton was isolated from Myrioneuron faberi. The structure and absolute configuration of 1 were elucidated by a combination of spectroscopic data, X-ray crystallographic, and computational methods. Myriberine A (1) demonstrated inhibition against the hepatitis C virus (HCV) life cycle in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Additionally, this compound demonstrated a hepatoprotective effect on treated cells ( Polyak et al, 2010 ). Myriberine A is an alkaloid isolated from Myrioneuron faberi and demonstrated inhibition against the HCV life cycle in vitro with a good therapeutic index (CC 50 /EC 50 ) of greater than 12.0 in vitro for non-cytotoxic concentration ( Huang et al, 2013 ). Oxymatrine and matrine are the two major alkaloid aqueous extracts from the Sophora root.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this compound demonstrated a hepatoprotective effect on treated cells ( Polyak et al, 2010 ). Myriberine A is an alkaloid isolated from Myrioneuron faberi and demonstrated inhibition against the HCV life cycle in vitro with a good therapeutic index (CC 50 /EC 50 ) of greater than 12.0 in vitro for non-cytotoxic concentration ( Huang et al, 2013 ). Oxymatrine and matrine are the two major alkaloid aqueous extracts from the Sophora root.…”
Section: Discussionmentioning
confidence: 99%
“…So is myriberine A. Additionally, myritonine C represents a unique trans-decahydroquinoline motif and possesses a rare cyano functionality. Both myritonine C (Li et al, 2016a) and myriberine A (Huang et al, 2013) showed inhibitory activity against hepatitis C virus.…”
Section: The Diversity Of Plant Natural Products In Southwest Chinamentioning
confidence: 99%
“…This alkaloid-an organic amine-contains a rearranged carbon skeleton and a nitrone moiety (Wang et al, 2007b). Many more novel organic amine-type alkaloids have been unveiled by the Hao laboratory ( Figure 1), e.g., α-myrifabrals A and B, β-myrifabrals A and B (Cao et al, 2014b), myritonines A−C (Li et al, 2016a), myrifabine (Cao et al, 2014a), and myriberine A (Huang et al, 2013) isolated from Myrioneuron faberi and M. tonkinensis (Rubiaceae). Myrifabrals and myritonines possess a novel cyclohexane-fused octahydroquinolizine and N-heterohexacyclic skeleton, respectively.…”
Section: The Diversity Of Plant Natural Products In Southwest Chinamentioning
confidence: 99%
“…(Rubiaceae) belong to the category of lysine-based structurally diverse natural products with various polycyclic skeletons (tricyclic-, tetracyclic-, pentacyclic-, hexacyclic-, octacyclic, and decacyclic-type), which have attracted much attention regarding their bioactivity and total synthesis [1][2][3][4][5][6][7][8][9][10][11][12][13]. In the past several years, we have isolated eighteen structurally unique and biosynthetically meaningful Myrioneuron alkaloids, including some with significant antihepatitis C virus (HCV) and antimicrobial activities [7][8][9][10][11][12]. In our continuing search for structurally unique and biologically active compounds, four new Myrioneuron alkaloids with cis-DHQ motif, mysumamides A-D (1-4) as well as three known ones, myrionamide (5), schoberine (6), and myrionidine (7) were isolated from the twigs and leaves of Myrioneuron effusum (Pitard) Li.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, we have isolated eighteen structurally unique and biosynthetically meaningful Myrioneuron alkaloids, including some with significant antihepatitis C virus (HCV) and antimicrobial activities [7][8][9][10][11][12]. In our continuing search for structurally unique and biologically active compounds, four new Myrioneuron alkaloids with cis-DHQ motif, mysumamides A-D (1-4) as well as three known ones, myrionamide (5), schoberine (6), and myrionidine (7) were isolated from the twigs and leaves of Myrioneuron effusum (Pitard) Li. Herein, we presented the isolation, structural elucidation, and bioactivity evaluation of these compounds.…”
Section: Introductionmentioning
confidence: 99%